Strategic Knowledge and Its Role in Talent Management in the Iraqi Industrial Sector - Ahmed, Hudhaifa Haitham; Hatem, Dellagi; Abdullah, Muhammad Ali; Mohammed, Qusay Jassim; Hamlaoui, Camelia (Journal of Posthumanism, 2025)
The study sought to investigate strategic knowledge by examining its components: the organizational environment, strategic priorities, organizational capabilities, and its influence on talent management. Talent management was assessed through exploratory talent and exploitative talent dimensions. The research was conducted on a group of employees from the Iraqi industrial sector. A descriptive-analytical method was used to gather, describe, and analyze data. The data was collected using a questionnaire as the main tool. A total of 250 randomly selected employees from the industrial sector participated in the study. Various statistical methods were employed to analyze the data and draw conclusions. These methods included Cronbach’s Alpha, arithmetic mean, standard deviation, Pearson’s correlation coefficient for examining relationships between variables, as well as t-tests, F-tests for assessing the significance of regression models, and R-squared.